Influence of viral infection in the healing process of periapical lesions: a narrative review (Research, Society and Development, 2021)
Background: Endodontic treatment aims to eliminate microorganisms and their toxic products, allowing the reestablishment of the host defenses and consequently, the healing of periapical tissues. However, numerous factors can affect periapical healing, such as the filling materials, the presence of microorganisms, systemic factors and, more recently, viral infections have been associated with the worsening of periapical lesions. Objective: To discuss the relationship between the main viral infections and the manifestations of apical periodontitis and how these infections can influence the repair of periapical tissues. Conclusion: The literature does not establish a cause-effect relationship between the presence of viruses in the periapical tissues and the increase in pathogenicity of the apical periodontitis. However, further studies should be conducted to affirm the viral potential in periapical tissues, since the literature shows an immune response in apical periodontitis triggered by viruses in the lytic phase, similar to that observed in other pathogens, which can exacerbate the inflammatory response, increase bone resorption and also interfere in the healing of periapical tissues.